PREDICTING THE RELATIONSHIP BETWEEN PERCEIVED INFLUENCE, BRAND ENGAGEMENT, BRAND EXPECTED VALUE AND INTENTION PURCHASE: AN EMPRICAL STUDY - Destian F Amaldi; Bella Sugita; Sabrina O. Sihombing (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The purpose of this study is to predict the relationship between perceived influence, brand engagement, brand expected value, and intention to purchase. The data were gathered from online respondents. The research questionnaire was built from previous research and the research variables were measured by 5-point Likert scales. Before analyzing data for testing hypotheses, reliability and validity tests are performed first. Hypothesis testing is conducted by using structural equation modeling.The results show that there are four out of six hypotheses that are supported. This paper provides research discussion, limitation, and recommendation for future research